What future for university training in translation professions? - Tomaszkiewicz, Teresa (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The world of translators, researchers in translation studies as well as the training of future professionals are currently going through several upheavals. The image of the competent translator is constantly changing. In the near future, he will be more and more confronted with new technologies which aim at the partial or even total replacement of his services by an automatic translation. At the moment the MT results are not completely satisfactory, but they are constantly improving. In this article the author first presents the evolution of translators’ competences to raise the question of the different professions of translation which require various skills and abilities. The second issue discussed concerns the influence of the pandemic on the training methods of future professionals and the possibility to benefit from these experiences.